Eksplorasi Potensi Pengembangan Wisata Alam Menggunakan Pendekatan 4A dalam Mendukung Pariwisata Berkelanjutan - Bagas Anggara; M.Taufik; Opan Satria Mandala (Yayasan Literasi Sains Indonesia, 2024)
Gunung Jae, Sedau Village, West Lombok, using the 4A approach (Accessibility, Attractions, Amenities, and Activities) as a conceptual framework. Qualitative research method with a narrative approach was employed in this case study, focusing on a deep and contextual understanding of natural phenomena in the research area. The results indicate that Gunung Jae offers various attractive natural attractions, including camping grounds, lakes, and refreshing green landscapes. However, the study also identifies challenges such as facility limitations, the need for improved accessibility, and the expansion of better environmental management. In an economic context, the research highlights the importance of empowering the local community through skills training and small business development. Additionally, social and cultural aspects are also addressed by respecting the authenticity of local culture and promoting intercultural understanding. Proposed improvement measures include enhancing amenity facilities, improving accessibility, empowering the local community, environmental protection, and cultural diversity promotion. Thus, Gunung Jae Sedau has the potential to become a model of sustainable tourism that not only provides economic benefits but also preserves environmental sustainability and strengthens local social and cultural values. This research provides valuable insights for stakeholders, local governments, destination managers, and the local community to plan and implement high-impact, sustainable development strategies in natural tourist destinations.